Information Disclosure in Innovation Contests - Thomas Rieck (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
In innovation contests, the progress of the competing firms in the innovation process is usually their private information. We analyze an innovation contest in which research firms have a stochastic technology to develop innovations at a fixed cost, but their progress is publicly announced. We make a comparison with the case of no information revelation: if the progress is disclosed, the expected profit of the firms is higher, but the expected profit of the sponsor is lower. Additionally, we show that firms may voluntarily reveal their information.
Keywords: O32; D82; D72; 330; Contest; innovation; information revelation; Innovationswettbewerb; Industrielle Forschung; Informationsverhalten; Theorie